Affective Memory in Gamified Learning: A Usability Study - Rodrigues, Luiz; Arndt, Daniel; Palomino, Paula; Toda, Armando; Klock, Ana Carolina Tomé; Avila-Santos, Anderson; Isotani, Seiji (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2022: Anais do XXXIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2022.225748, 2022)
Gamified learning has the potential to improve learning outcomes, but most strategies are focused on using Points-Badges-Leaderboards (PBL) while neglecting other game elements. Drawing upon research discussing nostalgia’s potential to improve user experience and engagement, we hypothesized affective memory could aid in designing gamification’s visual aesthetics. To start testing that hypothesis, we conducted a moderated usability study aiming to understand how Pokémon-based gamification compares to a trophy-based approach. Nine undergraduate students used two versions of a gamified quiz prototype (Pokémon and trophy-based) to complete multiple-choice items, then discussed their experiences in a semi-structured interview. Our findings suggest affective memory plays a significant role in gamified learning and indicate Pokémon-based gamification might maximize intrinsic motivation. Thus, informing practitioners that gamification targeting affective memory can enhance learning by increasing engagement and intrinsic motivation, and calling researchers to further investigate affective memory and other brands in gamification research.